The influence of high-level beliefs on self-regulatory engagement: evidence from thermal pain stimulation - Lynn, Margaret T.; Van Dessel, Pieter; Brass, Marcel (Frontiers in Psychology, 2013)
Determinist beliefs have been shown to impact basic motor preparation, prosocial behavior, performance monitoring, and voluntary inhibition, presumably by diminishing the recruitment of cognitive resources for self-regulation. We sought to support and extend previous findings by applying a belief manipulation to a novel inhibition paradigm that requires participants to occasionally suppress a prepotent withdrawal reaction from a strong aversive stimulus. Our results suggest that reduction of free will beliefs lead to a form of intentional disengagement that influences action selection and inhibition. It is likely that disbelief in free will encourages participants to be more passive, to exhibit a reduction in intentional engagement, and to be disinclined to adapt their behavior to contextual needs.